Are there differences between stemless and conventional stemmed shoulder prostheses in the treatment of glenohumeral osteoarthritis?. Issue 1 (December 2015) - Maier, Michael; Lauer, Sarah; Klotz, Matthias; Bülhoff, Matthias; Spranz, David; Zeifang, Felix
Abstract Background Conventional stemmed anatomical shoulder prostheses are widely used in the treatment of glenohumeral osteoarthritis. The stemless shoulder prosthesis, in contrast, is a new concept, and fewer outcome studies are available. Therefore, the purpose of the study was to investigate the early functional outcome and postoperative proprioception of a stemless prosthesis in comparison with a standard stemmed anatomic shoulder prosthesis. Methods Twelve patients (mean age 68.3 years [SD ± 5.4]; 5 female, 7 male) with primary glenohumeral osteoarthritis of the shoulder were enrolled, who underwent total shoulder arthroplasty (TSA) with a stemless total shoulder prosthesis, Total Evolution Shoulder System (TESS®; Biomed, France). The control group consisted of twelve (age and gender matched) patients (mean age 67.8 years; [SD ± 7.1]; 9 female, 3 male), getting a TSA with a standard anatomic stemmed prosthesis, Aequalis® Shoulder (Tournier, Lyon, France). Patients were examined the day before and six months after surgery. The pre- and postoperative Constant Score (CS) was evaluated and proprioception was measured in a 3D video motion analysis study using an active angle-reproduction (AAR) test. Results Comparing the postoperative CS, there was no significant difference between the groups treated with the TESS® prosthesis (48.0 ± 13.8 points) and the Aequalis® prosthesis (49.3 ± 8.6 points;p = 0.792). There was no significant difference in postoperative proprioception between the TESS® group (7.2° [SD ± 2.8]) and the Aequalis® group(8.7° [SD ± 2.7];p = 0.196), either. Comparison of in the results of CS and AAR test pre- and postoperatively showed no significant differences between the groups. Discussion In patients with glenohumeral osteoarthritis, treated with TSA, the functional and the proprioceptive outcome is comparable between a stemless and a standard stemmed anatomic shoulder prosthesis at early followup. Conclusion Further follow-up is necessary regarding the long-term performance of this prosthesis. Trial registration Current Controlled TrialsDRKS 00007528 . Registered 17 November 2014